Application of the Canva Application Media in Arabic Language Learning| Penerapan Media Aplikasi Canva dalam Pembelajaran Bahasa Arab - Rohmah, Nafi'atu; Izzah, Nailul; Ariliana (NAJAH BESTARI, 2024)
This research aims to evaluate the effectiveness of the Canva application as a learning medium in teaching Arabic. In the digital era, the integration of technology in education is very important to improve the quality of teaching and learning. Canva, as an online graphic design application, provides various templates and features that can be used to create visually attractive learning materials. This research uses a literature review method by analyzing literature related to the use of Canva in education. The tools used in this study were the results of in-depth interviews, where researchers asked open-ended questions to respondents to gain a deeper understanding of students' perspectives and participant observation was also an important tool, where researchers observed and perhaps took part in the daily activities of research subjects to gain direct insight. The research results show that Canva is effective in increasing students' interest and motivation to learn, creating interactive and innovative learning media, and simplifying the process of creating teaching materials. Canva has also proven helpful in clarifying concepts that are difficult to understand and improving student learning outcomes. Thus, using Canva as a learning medium can provide significant benefits in teaching Arabic.